2017
DOI: 10.1038/cddis.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 regulates resident macrophages by protecting lysosomal integrity

Abstract: Hematopoietic cell survival and death is critical for development of a functional immune system. Here, we report that a protein kinase, TAK1, is selectively required for resident macrophage integrity during embryogenesis. Hematopoietic lineage-specific deletion of Tak1 gene (Tak1HKO) caused accumulation of cellular debris in the thymus in perinatal mice. Although no overt alteration in thymocytes and blood myeloid populations was observed in Tak1HKO mice, we found that thymic and lung macrophages were diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…Our study identified several important effector molecules driving this cell death and inflammation downstream of TAK1-inactivation and hence potential therapeutic targets. Increased cell death of TAK1-deficeint resident macrophages has also been observed in in vivo mouse models with hematopoietic specific deletion of TAK1 ( Sakamachi et al, 2017 ). Future studies will test whether similar pathways of cell death and inflammasome activation, as established in our study, are at work in these resident macrophages.…”
Section: Resultsmentioning
confidence: 89%
“…Our study identified several important effector molecules driving this cell death and inflammation downstream of TAK1-inactivation and hence potential therapeutic targets. Increased cell death of TAK1-deficeint resident macrophages has also been observed in in vivo mouse models with hematopoietic specific deletion of TAK1 ( Sakamachi et al, 2017 ). Future studies will test whether similar pathways of cell death and inflammasome activation, as established in our study, are at work in these resident macrophages.…”
Section: Resultsmentioning
confidence: 89%
“…To investigate changes in the peripheral immune compartment, the spleen of the TAK1 Δ M and control mice was immunophenotyped at day 3 post-stroke. Previous studies have shown that cell type and tissue-specific TAK1 deletion increases cell death in multiple cells and tissues including hematopoietic cells, monocytes, epidermis, and intestinal epithelium [ 14 , 32 , 35 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of TAK1 from neutrophils and monocyte/macrophages also microglia (Additional file 3 : Figure S3), resulted in high circulating neutrophils, monocytes, and animals develop splenomegaly [ 17 ]. Tissue-specific deletion of TAK1 caused cell death in tissues including epidermis, intestinal epithelium, hepatocytes, and osteoblasts [ 32 , 42 ]. Interestingly, myeloid-specific TAK1 deletion did not induce cell death in our study, a finding also seen by others [ 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, hydrolase depletion could stem from transcriptional inhibition or from their defective trafficking to the lysosome (Kobayashi et al, 1999;Saftig and Klumperman, 2009;Sleat et al, 2013). Alternatively, it is tempting to speculate that the increased propensity of NPC lysosomes to undergo membrane damage could result in leakage of lumenal contents, including resident hydrolases, a phenomenon suggested to occur in NPC as well as other physiological and pathological contexts (Chung et al, 2016;Hämälistö et al, 2020;Maejima et al, 2013;Sakamachi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%